میرؔ کا سوانحی ارتقاء اور ہندوستان کا تہذیبی و سیاسی منظر نامہ (Al-Aasar, 2025)
Mir Taqi Mir (1723-1810) was a great poet of the declined  period  of  Mughal Empire.   Most of his life spent in Delhi and Lucknow.   Mir was born in Agra, but his father died soon, which caused him to face economic difficulties.  Mir spent some time in Delhi, but due to political instability and economic misery, he had to leave Delhi. He moved to Lucknow, where he spent the rest of his life.   Mir's poetry shows the suffering and problems of his personal life. He mentioned the destruction of Delhi in his poetry, the fall of the Mughal Empire and the helplessness of the common people.  Mir's poetry is still a valuable asset of Urdu literature.